Immunogenicity, efficacy, and safety of CoronaVac and Pfizer/BioNTech mRNA vaccines in patients with psoriasis receiving systemic therapies: A prospective cohort study - AY, NADİYE PINAR (My University, 2023)
Background and objectives: Evidence of immune response to COVID-19 vaccine in psoriasis patients on biological agents is lacking. This study aimed to evaluate SARS-CoV-2 antibody levels following vaccination with CoronaVac or Pfizer/BioNTech mRNA in patients using biological agents or methotrexate, hightiter antibody levels achievement rate, and impact of medications on immunogenicity. Methods: This noninterventional, prospective cohort study included 89 patients and 40 controls vaccinated with two doses of inactivated (CoronaVac) or Pfizer/BioNTech mRNA vaccines. Anti-spike and neutralising antibodies were analysed before and three to six weeks after the second dose. Adverse effects and symptomatic COVID-19 were assessed. Results: Median anti-spike and neutralising antibody titers after CoronaVac were significantly lower in patients than controls (57.92 U/mL vs 125.4 U/mL, and 1/6 vs 1/32, respectively, p < 0.05). Patients were less likely to achieve high-titer anti-spike antibody levels (25.6 % vs 50 %). Infliximab was associated with attenuated vaccine response. Pfizer/BioNTech vaccine induced comparable median anti-spike (2,080 U/mL vs 2,976.5 U/mL,) and neutralising antibody levels (1/96 vs 1/160) in patients and controls, respectively (p > 0.05). High-titer anti-spike and neutralising antibodies development rates were comparable among patients and controls (95.2 % vs 100 %, and 30.4 % vs 50.0 %, respectively, p > 0.05). Nine (10.1 %) COVID-19 cases- all mild - were identified. Psoriasis flare was seen in 6.74 %, mostly after Pfizer/BioNTech vaccine. Conclusion: Psoriasis patients treated with biological agents and methotrexate developed similar response to mRNA vaccine but weaker response to inactivated vaccine. Infliximab reduced response to the inactivated vaccine. Adverse effects were more frequent with mRNA vaccine, but none was severe
Keywords: Psoriasis; Biologics; COVID-19; Vaccination; antiTNF; anti-IL17